2020
DOI: 10.1080/14767058.2020.1777271
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiles of mid-trimester amniotic fluid are not associated with subsequent spontaneous preterm delivery or gestational duration at delivery

Abstract: Introduction: Spontaneous preterm delivery (<37 gestational weeks) has a multifactorial etiology with still incompletely identified pathways. Amniotic fluid is a biofluid with great potential for insights into the feto-maternal milieu. It is rich in metabolites, and metabolic consequences of inflammation is yet researched only to a limited extent. Metabolomic profiling provides opportunities to identify potential biomarkers of inflammatory conditioned pregnancy complications such as spontaneous preterm deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Interestingly, as previously discussed, a recent study [16] found no significant differences in metabolite profiles associated with spontaneous PTD. This outcome may be attributed to variations in stratification and research protocols.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, as previously discussed, a recent study [16] found no significant differences in metabolite profiles associated with spontaneous PTD. This outcome may be attributed to variations in stratification and research protocols.…”
Section: Discussionsupporting
confidence: 53%
“…Research studies [11][12][13][14][15] suggest that conducting a metabolomic analysis on AF obtained during the prenatal period holds the potential to identify metabolic deviations before PTD occurs. However, a recent study using untargeted LC-MS mid-trimester amniotic fluid metabolic profiling on two groups of 37 pregnant women (full term/preterm) that underwent amniocentesis showed no evidence of metabolite differentiation for spontaneous PTD [16].…”
Section: Introductionmentioning
confidence: 96%
“…The method used in this study [ 30 ] was first developed on a HILIC system comprised of UHPLC with detection on a triple quadrupole mass spectrometer operating in both positive and negative electrospray ionization modes and validated with amniotic fluid samples from 250 second-trimester pregnant women [ 31 ]. On the contrary, based on mid-trimester metabolic profiling, there was no evidence of grouping about spontaneous preterm delivery according to a very recent study using untargeted LC-MS amniotic fluid metabolomic profiling [ 32 ]. Perhaps, extended targeted analysis on multiple pregnancy time points could offer clarification, but it is rather challenging due to the invasive sample collection method of amniocentesis.…”
Section: Reviewmentioning
confidence: 99%